2022
DOI: 10.1186/s43058-022-00315-0
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of champions in implementing innovations in health care: a systematic review

Abstract: Background Champions have been documented in the literature as an important strategy for implementation, yet their effectiveness has not been well synthesized in the health care literature. The aim of this systematic review was to determine whether champions, tested in isolation from other implementation strategies, are effective at improving innovation use or outcomes in health care. Methods The JBI systematic review method guided this study. A pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 101 publications
1
42
0
Order By: Relevance
“…In fact, the VALENF Instrument is currently being implemented in the electronic clinical records of the hospital where it was developed. Due to the reliability results, interventions based on previous studies are being carried out, such as including help text on how to assess and interpret the items in the programming [ 38 ], setting up a team of assistants that will help in the implementation of the VALENF Instrument [ 39 ], carry out specific training [ 40 ] or schedule reassessment alerts [ 41 ]. Future studies should explore the opinion of nurses on the usefulness and applicability of the VALENF Instrument and other similar tools that may begin to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the VALENF Instrument is currently being implemented in the electronic clinical records of the hospital where it was developed. Due to the reliability results, interventions based on previous studies are being carried out, such as including help text on how to assess and interpret the items in the programming [ 38 ], setting up a team of assistants that will help in the implementation of the VALENF Instrument [ 39 ], carry out specific training [ 40 ] or schedule reassessment alerts [ 41 ]. Future studies should explore the opinion of nurses on the usefulness and applicability of the VALENF Instrument and other similar tools that may begin to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a strong rationale for the use of a clinician champion as a de-implementation strategy [ 24 ], few studies have employed them to address low-value care, although Colla and colleagues identified strategies that champions might employ such as clinician education and provider feedback as effective [ 34 ]. Santos and colleagues recently completed a systematic review of the effectiveness of a clinician champion when implementing an innovation into health care settings [ 35 ]. Only one of the 35 studies included in the review was focused on de-implementing a low-value care service, that of urinary catheters in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is surprisingly little research defining the concept of 'change champion,' and evaluating the impact of change champions on healthcare implementation efforts. Often research on champions is only descriptive in nature, lacking in detail, or the findings are embedded within broader, complex implementation efforts that cannot isolate the individual effect of the champions (Miech et al, 2018;Santos et al, 2022;Shea, 2021). To illustrate, two reviews on champions in healthcare implementation reported that the vast majority of articles only considered champions in terms of presence or absence (more than 90% of 199 articles (integrative review) (Miech et al, 2018), 71% of 35 articles (systematic review of quantitative research only) (Santos et al, 2022).…”
Section: What Did We Do?mentioning
confidence: 99%
“…Often research on champions is only descriptive in nature, lacking in detail, or the findings are embedded within broader, complex implementation efforts that cannot isolate the individual effect of the champions (Miech et al, 2018;Santos et al, 2022;Shea, 2021). To illustrate, two reviews on champions in healthcare implementation reported that the vast majority of articles only considered champions in terms of presence or absence (more than 90% of 199 articles (integrative review) (Miech et al, 2018), 71% of 35 articles (systematic review of quantitative research only) (Santos et al, 2022). Santos and colleagues' (2022) systematic review of quantitative research related to healthcare champions reported that though champions were related to increased use of healthcare innovations at an organisational level (i.e.…”
Section: What Did We Do?mentioning
confidence: 99%